Antecedents of internationalization in family firms - Bayık, Ali Mert. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The current research analyzed the antecedents of internationalization in family firms. The following research aims to analyze how different firm-level antecedents associates with the internationalization of family firms in Turkey. The survey was sent to 312 firms and 145 responses have been collected. Out of the received responses, 43 were eliminated since the respondents' credentials were not meeting the inclusion criteria. Hence, 102 responses were selected. However, five responses with outlier values have been eliminated and 97 responses were analyzed via statistical means using SPSS 27. The survey was developed by analyzing the previous work of scholars critically in order to gain relevant results. Independent variables used in this study were the firm’s age, firm size, family share ownership, R&D intensity, and international experience. The association of these independent variables with the internationalization of family firms was analyzed. The research was quantitative, and an online survey method was used for data collection. The research findings showed that firm size has a significant positive association with the internationalization of family firms. In contrast firm age, family ownership, R&D intensity, international experience have no significant association with the internationalization of family firms in Turkey.
Keywords: Family-owned business enterprises -- Turkey.